ATTENUATION OF CARBON TETRACHLORIDE AND ETHANOL-INDUCED HEPATIC FIBROSIS IN RATS BY CALLIGONUM COMOSUM SHOOT EXTRACT - Hassan, Sherien Kamal; Mousa, Amria Mamdouh; El-sammad, Nermin Mohammed (Asian Journal of Pharmaceutical and Clinical Research, 2017)
ABSTRACT Objective: This study was designed to evaluate the hepatoprotective and antioxidant effects of methanolic extract of Calligonum comosum (C. comosum) shoots on the hepatic fibrosis induced by carbon tetrachloride and ethanol (CCl4/ethanol) in rats. Methods: A liver fibrosis was induced in Sprague Dawley rats by oral administration of CCl4 (1 ml/kg body weight, twice weekly for 10 weeks) along with ethanol (10% in drinking water 1 week before CCl4 administration and throughout the experiment). Rats were pretreated with C. comosum extract (daily, orally at a dose of 50 mg/kg body weight 1 week before CCl4 administration). At the end of the experiment, serum, and liver samples were subjected to biochemical investigations. In addition, liver and kidney tissues were evaluated for histopathological changes. Results: C. comosum extract pretreatment significantly reduced CCl4 - induced elevation in serum levels of aspartate aminotransaminase, alanine aminotransaminase, alkaline phosphatase, total bilirubin, urea, creatinine, and significantly elevated serum contents of total protein and albumin, as well as an improvement in hepatic protein content, albumin/globulin ratio, body weight and relative liver and kidney weights. C. comosum extract also significantly increased the hepatic levels of glucose-6-phosphatase, glutathione peroxidase, glutathione-S-transferase, catalase, superoxide dismutase, and glutathione with significant decrease in the contents of malondialdehyde and protein carbonyl. In addition, downregulation in expression of the fibrotic marker matrix metalloproteinase-2 was observed. C. comosum extract also ameliorated histopathological changes of CCl4/ethanol group which further evidenced the biochemical findings. Conclusion: Our results confirmed that the methanolic extract of C. comosum shoots effectively protect against CCl4/ethanol-induced liver fibrosis, through its antioxidant property. Keywords: Calligonum comosum, Hepatic fibrosis, Carbon tetrachloride, Hepatoprotective effect, Antioxidants, Matrix metalloproteinase-2.